Correlation of BOS process variables with dust mass formation and zinc content. (August 2014) - Steer, J.; Griffiths, A.; Heinrich, T.; Thomas, A.; Barnes, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The basic oxygen steelmaking (BOS) process typically produces a dust rich in valuable iron units and often contaminated with zinc. This paper takes a look at statistical correlation and multiple regressions of process variables with the quantity of dust and the zinc mass contained in the dust. A robust inline sampling system was designed and installed to isokinetically sample the primary BOS dust slurry from a 248 m3 capacity BOS converter at Tata Steelworks Port Talbot (UK). This system was used to measure the dust mass and composition changes against time for 12 large scale trial heats and to compare with the process information data for a statistical evaluation of the variables. Statistically significant Pearson linear correlations were measured for the total dust mass produced with the iron ore and for the zinc mass contained in the dust with the addition of waste oxide briquettes (WOBs). A multiple regression analysis model showed strong associated correlations between the zinc mass contained in the dust with the galvanised scrap and WOB additions and explained 73% of the zinc mass variance.